STRUCTURE OF INVESTMENT COSTS OF DAIRY SHEEP BREEDING FARMS IN BULGARIA - Tsvetana HARIZANOVA – METODIEVA; Nikola METODIEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the research was to analyze the structure of the investment costs for the establishment of dairy sheep breeding farms in Bulgaria, as well as to explore some indicators, characterizing the activity of the farms under this study. The data were collected by visiting and questioning the owners of 5 sheep farms and on the basis of own calculations. The structure of the investment costs of the dairy sheep farms was explored. The amount of investments per 1 ewe in each farm was also calculated. Average milk yield, age of inclusion in the main flock of ewes and rams, average number of lactations of ewes, average number of years of using rams and prolificacy were analyzed. Although we couldn’t prove it statistically, we saw a tendency for reduction of the investment costs per 1 ewe with an increase in the number of animals in the main flock. The largest share of the investments occupied the purchase of animals, followed by the land purchase and the expenses for agricultural buildings. The interviewed farmers bought predominantly used tractors and other agricultural machinery, mainly because of their lower prices. The ewes in the five farms were inseminated naturally. They were kept in renovated old buildings. During the summer season, the animals grazed on pastures; concentrated fodder as a supplement was used in only one of the farms. The farmers used their agricultural lands mainly to produce meadow hay and alfalfa occasionally wheat and barley. The average milk yield in the farms ranged from 80 to 170 liters per year. These large ranges of variation were due both to the raised sheep breeds and to the specifics farms’ activities. Nulliparous ewes and rams were included in the main flock at 12-18 months of age. The sheep remained in the main flock on average of 6 lactations with a variation from 5 to 8 lactations. The rams were used on average for 2 years with variations from 1 to 4 years. Prolificacy in the farms ranged from 100 to 154%.